PROBLEMATIKA SUMBER DAYA MANUSIA (SDM) DI SEKOLAH DASAR YANG TERLETAK DI DAERAH TERPENCIL - Haji, Son (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This journal describes the problem of human resources (HR) in elementary schools located in remote areas. The success of an education will not be separated from the human resources that play the role of the teacher or the teaching staff. Elementary School is an education level that lasts for the longest, which is 6 years, where the level of low level formal education is determined by the formation of character in the future students. This type of research was conducted with a qualitative descriptive approach with a type of case study. Pulau Rimau Public Elementary School 1 has 8 educators with 1 school principal where there are only 4 educators who are undergraduate graduates (S1) and 4 others are high school graduates, this is due to the fact that the region is located in a remote area namely Penuguan Village, Pulau Rimau District, Banyuasin Regency, South Sumatra which is located in the waters and far from the city center. In addition, the number of students in the 2018/2019 academic year from class I to VI is 156 people. Educators must have appropriate qualifications that help improve the ability of students or at least to be able to teach at the elementary school level must be a graduate (S1).